Response to fertilizer of native grasses (Pennisetum polystachion and Setaria sphacelata) and legume (Tephrosia pedicellata) of savannah in Sudanian Benin - KINDOMIHOU, Missiakô Valentin; SAIDOU, ALIOU; SINSIN, Brice Augustin (My University, 2014)
Response to nitrogen fertilizer of 2 grass species, Pennisetum polystachion and Setaria sphacelata, and one legume Tephrosia pedicellata was studied in northern Benin. The 3 species are native in Sudanian grasslands and occur on tropical ferruginous soils. The experimental plots were fertilized with a basal dressing of potassium chloride and triple superphosphate before testing nitrogen fertilizer at rates of 0, 60 and 120 kg/ha N, respectively. The highest biomass was produced with 120 kg/ha (4.98, 2.13 and 1.1 t/ha DM for Pennisetum, Setaria and Tephrosia, respectively). The highest number of pods per plant with Tephrosia was produced with the control plot (35.75 pods per plant) and the lowest with an N rate of 60 kg/ha (23.75 pods per plant). The highest tussock diameters for Setaria and Pennisetum were 76.4 and 71.9 cm, respectively, at an N rate of 120 kg/ha. These 3 native forage species showed good performance under cultivation.
Keywords: Grass; Legume; Nitrogen Fertilizer; Savanna; Benin